Political discussion and news use in the contemporary public sphere - Brundidge, Jennifer (Javnost (Ljubljana), 2010)
This article is directed toward understanding the impact of Internet use on the accessibility of politically relevant online discourse (news and political discussion) and about the extent to which these forms of discourse are meaningfully and intimately connected. Through the use of nationally representative survey data, findings suggest: (1) when compared to offline counterparts, SES and political knowledge are equally, if not more relevant to frequent use of online news and engagement in online political discussion, suggesting that Internet use has contributed to a slightly less accessible public sphere; (2) when compared to offline counterparts, the relationship between online news and online discussion is the strongest, suggesting an especially intimate and important connection between the two forms of discourse.
Keywords: politične komunikacije; javnost; javna sfera; informiranje; elektronski mediji; internet